The urokinase-type plasminogen activator, its inhibitors and its receptor - the new prognostic factors in solid cancers - Borštnar, Simona (Radiology and oncology (Ljubljana), 1997)
The urokinase-type plasminogen activator (uPA), its inhibitors (PAI-1 and PAI-2) and its receptor (uPAR) play nan important role in the degradation of the intercellular tissue, the process which affects the ability of cancer cells to invade to surrounding tissue and to metastasize. The results of clinical studies performed in the past few years point out a significant influence of uPA, PAI-1, PAI-2 and uPAR on the course of the disease and survival of patients with solid tumours, particularly breast cancer. Hopefullythe categorization of patients according to the content of the serineproteases and its inhibitors in tumour tissues could provide a basis formore rational treatment planning and thus improving patients' survival.
Keywords: onkologija; rak (medicina); zdravljenje